Ku śmierci ze skazą „niegotowości”? — o kilku czytelniczych spojrzeniach na Sérénité Jarosława Iwaszkiewicza - Berkan-Jabłońska, Maria (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2012)
This article proposes to read Iwaszkiewicz’s story titled Sérénité with more suspicion than it has been done in a traditional, usually enthusiastic reception of this prose. Firstly, the text presents typical approaches to interpretation. The main part of the article suggests certain textual qualities which may cause feel “discomfort” in the modern reader.According to the author of the paper, there is something anachronistic in the story. The story was written a long time ago and therefore the style of narration, the elements of camouflage and sophisticated tricks may seem inappropriate for such a serious subject as death.Also, the construction of the narrator and hero who is always passive, unwilling to act and focused on his inner life may today seem irritatingly anachronistic, oldfashioned and incomprehensible.These arguments are used to show that a critical analysis of the novel, due to new readers’ awareness, can surprisingly lead to interesting questions and open new paths of interpretation.